2016
DOI: 10.3920/bm2015.0154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GABA and GABA-producing Lactobacillus brevis DPC 6108 on the development of diabetes in a streptozotocin rat model

Abstract: The aim of this study was to investigate if dietary administration of γ-am inobutyric acid (GABA)-producing Lactobacillus brevis DPC 6108 and pure GABA exert protective effects against the development of diabetes in streptozotocin (STZ)-induced diabetic Sprague Dawley rats. In a first experiment, healthy rats were divided in 3 groups (n=10/group) receiving placebo, 2.6 mg/kg body weight (bw) pure GABA or L. brevis DPC 6108 (-'109 microorganisms). In a second experiment, rats (n=15/group) were randomised to fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 54 publications
1
32
0
2
Order By: Relevance
“…In a previous study showed that the γ-aminobutyric acid (GABA)-producing Lactobacillus brevis DPC 6108 and pure GABA has protective effects against the development of diabetes in STZ-induced diabetic Sprague Dawley rats. In this study, glucose levels were decreased in diabetic rats receiving L. brevis DPC 6108, compared with diabetic controls (Marques et al, 2016). In addition, oral administration of L. paracasei TD062 induced α-glucosidase inhibitory activity and ameliorated lipid metabolism, oxidative stress, and glucose metabolism (Dang et al, 2018).…”
Section: Tea Polysaccharides As Antidiabetic Supplementmentioning
confidence: 55%
“…In a previous study showed that the γ-aminobutyric acid (GABA)-producing Lactobacillus brevis DPC 6108 and pure GABA has protective effects against the development of diabetes in STZ-induced diabetic Sprague Dawley rats. In this study, glucose levels were decreased in diabetic rats receiving L. brevis DPC 6108, compared with diabetic controls (Marques et al, 2016). In addition, oral administration of L. paracasei TD062 induced α-glucosidase inhibitory activity and ameliorated lipid metabolism, oxidative stress, and glucose metabolism (Dang et al, 2018).…”
Section: Tea Polysaccharides As Antidiabetic Supplementmentioning
confidence: 55%
“…Several important physiological functions of GABA have been characterized, such as neurotransmission, induction of hypotension, diuretic effects, antidiabetic, relaxing and tranquilizer effects (Inoue et al, 2003; Marques et al, 2016). In fact, some GABA A -receptor agonist drugs (e.g., benzodiazepines) are important pharmacological agents used for clinical treatment of anxiety (Foster and Kemp, 2006).…”
Section: Biofunctional Foodsmentioning
confidence: 99%
“…Lactobacilli have the necessary capacity to produce GABA and do to varying extents depending upon the individual strain and the environment. Indeed, the GABA-producing Lactobacillus brevis DPC 6108 strain has recently been shown to alter the development of diabetes in a streptozotocin rat (Marques et al, 2016).…”
Section: Microbiota and Humoral Responsesmentioning
confidence: 99%